Influence of extended aging on beef quality characteristics and sensory perception of steaks from the biceps femoris and semimembranosus. (September 2016) - Colle, M.J.; Richard, R.P.; Killinger, K.M.; Bohlscheid, J.C.; Gray, A.R.; Loucks, W.I.; Day, R.N.; Cochran, A.S.; Nasados, J.A.; Doumit, M.E.
Abstract: The objective was to determine the influence of post-fabrication aging (2, 14, 21, 42, and 63 days) on beef quality characteristics and consumer sensory perception of biceps femoris (BF) and semimembranosus (SM) steaks. Lipid oxidation and aerobic plate counts increased ( P  < 0.05) with longer aging periods and retail display times. An aging period by day of retail display interaction ( P  < 0.05) was observed for a* and b* values of the BF and SM. Warner–Bratzler shear force values decreased ( P  < 0.05) with longer aging for the SM, while no difference was observed for the BF. Consumer panel results revealed that longer aging periods increased ( P  < 0.05) acceptability of the SM, tenderness of both muscles, and tended to increase ( P  = 0.07) juiciness of the SM. Our results show that extended aging reduces retail color stability yet has positive effects on consumer perception of tenderness of both muscles and overall acceptability of the SM. Highlights: USDA Select beef bottom round and top rounds were aged for up to 63 days. Aging for 14 to 21 days optimizes consumer perception of bottom round tenderness. Perception of top round tenderness is optimized between 21 and 42 days of aging. Extended aging reduces retail shelf-life of the biceps femoris and semimembranosus .